A History of Everyday Life in Scotland, 1800 to 1900 - Morton, Graeme (A History of Everyday Life in Scotland, 2022)
This volume explores the experience of everyday life in Scotland over two centuries characterised by political, religious and intellectual change and ferment. It shows how the extraordinary impinged on the ordinary and reveals people's anxieties, joys, comforts, passions, hopes and fears. It also aims to provide a measure of how the impact of change varied from place to place.The authors draw on a wide range of primary and secondary sources, including the material survivals of daily life in town and country, and on the history of government, religion, ideas, painting, literature, and architecture. As B. S. Gregory has put it, everyday history is 'an endeavour that seeks to identify and integrate everything - all relevant material, social, political, and cultural data - that permits the fullest possible reconstruction of ordinary life experiences in all their varied complexity, as they are formed and transformed.'